2017
DOI: 10.24990/injec.v2i1.122
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Transcultural Nursing Model in Perspective of Madura Culture Improving Breastfeeding Mother’s Behavior in Jember

Abstract: ABSTRAKPendahuluan: Menyusui merupakan salah satu tugas perkembangan perempuan setelah melahirkan. Banyak faktor yang dapat mempengaruhi keberhasilan ibu dalam memberikan ASI secara ekslusif, diantaranya adalah dukungan keluarga maupun pengaruh budaya lokal. Tujuan Penelitian ini untuk menerapkan model keperawatan transkultural dalam perspektif budaya Madura pada ibu menyusui. Metode : Penelitian ini dilakukan di desa Suboh wilayah kerja Puskesmas Pakusari, pengumpulan data menggunakan kuesioner, dan fokus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It could be seen from the research that the results showed that only 21.1% of mothers gave breastfeeding exclusively to their babies, while mothers who received the Leininger's Transcultural-based GATHER Counseling Model were 81.6%. One of the techniques used was cultural modification with the application of Leinenger's transcultural theory to increase breast milk production (5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be seen from the research that the results showed that only 21.1% of mothers gave breastfeeding exclusively to their babies, while mothers who received the Leininger's Transcultural-based GATHER Counseling Model were 81.6%. One of the techniques used was cultural modification with the application of Leinenger's transcultural theory to increase breast milk production (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is the biggest case suffered by infants as a result of non-exclusive breastfeeding (4) . Besides, the growth and development of babies can experience delays due to inadequate nutrition received (5) . Of course, this has a negative effect on the quality of future Indonesia's human resources.…”
Section: Introduction Backgroundmentioning
confidence: 99%